Propranolol and prednisolone combination for the treatment of segmental haemangioma in PHACES syndrome. (18th May 2015) - Gnarra, M.; Solman, L.; Harper, J.; Batul Syed, S.
Summary Posterior fossa malformations–haemangiomas–arterial anomalies–cardiac defects–eye abnormalities–sternal cleft and supraumbilical raphe syndrome (also known as PHACES syndrome) is a rare neurocutaneous disorder. Children presenting with these manifestations need careful ophthalmological, cardiac and neurological assessment. They may have one or more of these extracutaneous manifestations, the most common being cerebral and cardiovascular anomalies. There is controversy about treating these children with propranolol especially if they have cerebrovascular involvement with narrow, dysplastic or absent blood vessels. The concern with propranolol is that hypotension may lead to reduced cerebral blood flow and neurological consequences. Prior to propranolol the systemic treatment for haemangiomas was prednisolone and then the concern was the opposite, namely hypertension. Our proposal was whether a combination of these two drugs would provide a safer and faster recovery. We report three retrospective cases of PHACES syndrome, each of whom received treatment with a combination of propranolol and prednisolone: two children were started on prednisolone and propranolol was added because the haemangiomas failed to respond adequately; the third child was started on propranolol and developed peripheral ischaemia and ulceration necessitating a reduction in dose addition of a low dose of prednisolone. All three patients, who failed on the one treatment, responded well to combination therapy without any significant complications. These outcomes suggest that for some patients with PHACES syndrome the use of combination treatment with propranolol and prednisolone could be advantageous, potentially allowing for the introduction of low doses of each with an enhanced combined effect. The doses can be increased gradually depending on the magnetic resonance imaging findings.